Some results on certain subclasses of analytic functions involving generalized hypergeometric functions and Hadamard product - Khalida Inayat Noor (International Journal of Mathematics and Mathematical Sciences)
By using a certain linear operator defined by a Hadamard product or convolution, several interesting subclasses of analytic functions in the unit disc are introduced and some unifying relationships between them are established. A variety of characterization results involving a certain functional and some general functions of hypergeometric type are investigated for these classes.